Assessing the gene regulatory properties of Argonaute-bound small RNAs of diverse genomic origin - Thomson, Daniel W. (Nucleic Acids Res, 2015)
High-throughput sequencing reveals an abundance of microRNA-sized fragments derived from larger non-coding RNAs. Roles for these small RNAs in gene silencing are suggested by their co-precipitation with Argonaute, the microRNA effector protein, though the extent to which they suppress gene expression endogenously remains unclear. To address this, we used luciferase reporters to determine the endogenous functionality of small RNAs from a diverse range of sources. We demonstrate small RNAs derived from snoRNAs have the capacity to act in a microRNA-like manner, though we note the vast majority of these are bound to Argonaute at levels below that required for detectable silencing activity. We show Argonaute exhibits a high degree of selectivity for the small RNAs with which it interacts and note that measuring Argonaute-associated levels is a better indicator of function than measuring total expression. Although binding to Argonaute at sufficient levels is necessary for demonstrating microRNA functionality in our reporter assay, this alone is not enough as some small RNAs derived from other non-coding RNAs (tRNAs, rRNAs, Y-RNAs) are associated with Argonaute at very high levels yet do not serve microRNA-like roles.